PENGARUH PENERAPAN STRATEGI TIPE INDEX CARD MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 SUNGAI AUR KABUPATEN PASAMAN BARAT - Aryanti, Aryanti; Rahmi, Rahmi; Haryono, Yulia (STKIP PGRI Sumbar, 2013)
This research is lower of studentsâ understanding of mathematical concept Â comprehension at eighth grade students of SMPN 1 west Pasaman and lack to given chance for approach their idea in learning process. One of step the problem by using type Index Card Match (ICM) strategy in learning mathematics. So this research is aim to know studentâs understanding of mathematical by using Type Index Card Match (ICM) Strategy was better than conventional learning toward studentâs at eighth grade SMPN 1 Sungai Aur west Pasaman. Population in this research is the eight class student of SMPN 1 Sungai Aur west Pasaman academic year of 2012/2013. The sample is taken randomly. The experiment class is VIII5 and the control class VIII1. The instrument in this research is mathematical concept understanding test like esay. Data by analysis with using test normality, test homogeneity and t-test. The researcher to analyse the data, the researcher got the result post test which using the students understanding of mathematical concept the experiment class is 73,62 and the control class is 63,61. Hypothesis test is using MINITAB with t-test, got probabilitas = 0,002 is smaller than Â 0,05. Then it can be concluded that studentâs understanding of mathematical concept using active learning type Index Card Match (ICM) strategy is be better than conventional learning toward studentsâ at eighth grade SMPN 1 Sungai Aur west Pasaman.